2017
DOI: 10.1159/000475992
|View full text |Cite
|
Sign up to set email alerts
|

Global Application of the Assessment of Communication Skills of Paediatric Endocrinology Fellows in the Management of Differences in Sex Development Using the ESPE E-Learning.Org Portal

Abstract: Background: Information sharing in chronic conditions such as disorders of/differences in sex development (DSD) is essential for a comprehensive understanding by parents and patients. We report on a qualitative analysis of communication skills of fellows undergoing training in paediatric endocrinology. Guidelines are created for the assessment of communication between health professionals and individuals with DSD and their parents. Methods: Paediatric endocrinology fellows worldwide were invited to study two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The creation of multidisciplinary teams dedicated to the management of DSD conditions worldwide poses its own challenges. Apart from economical limitations and practical hurdles, training of staff with respect to the acquisition of knowledge, as well as communication skills, is an ongoing endeavour 159 . Examples that outline the role of team members as well as team responsibilities are available 28,160 .…”
Section: Discussionmentioning
confidence: 99%
“…The creation of multidisciplinary teams dedicated to the management of DSD conditions worldwide poses its own challenges. Apart from economical limitations and practical hurdles, training of staff with respect to the acquisition of knowledge, as well as communication skills, is an ongoing endeavour 159 . Examples that outline the role of team members as well as team responsibilities are available 28,160 .…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that the health provider's communication skills affect parents' decision-making processes [53]. These skills vary wildly, even amongst DSD specialists [54]. While the developed tool for professionals outside the DSD center encompasses tips on how to communicate with the family, no advice on this matter was included in the material for the multi-professional team in the DSD center.…”
Section: Discussionmentioning
confidence: 99%
“…While some resources are designed for the purposes of providing quick access to high-yield information such as the Peds Cardiology Handbook app (Rochelson et al 2022), others are targeted towards a wider audience and take the form of written, audio and video content, as discussed in Martiniuk et al’s study (2022). Resources have also been created to provide training in areas of paediatrics that traditionally take place face-to-face, such as paediatric resuscitation (O’Leary 2012) and communication (Kranenburg et al 2017). Both studies found this mode of teaching to be effective in improving knowledge and competence in their respective areas among healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%